EKSPRESI IDIOMATIK DALAM LIRIK “NINE TRACK MIND” CHARLIE PUTH ALBUM 2016 - varia virdania virdaus (MOTORIC, 2020)
Language is used for communication which allows people say things to each other and express their communicative needs. Language learners are aware that to understand the informal form of conversation used by native speakers of English, they need information and guidance to assist them in using the appropriate idioms in a given situation. English songs are one of the media of introducing and reviewing vocabulary, including idiomatic expressions. The purpose of this study is to find out and explain the meaning of idiomatic expressions in Charlie Puth’s song lyrics in album Nine Track Mind 2016. The type of data used in this study was a descriptive quantitative method because to the point out about collects, analysis, describes, identifies the idiomatic expression in Charlie Puth’s album, and to count of idiomatic expression. Key Words: Idiom, Lyric, Charlie Puth, Nine Track Mind Album